ENGLISH LINGUISTIC LANDSCAPE AND EFL LEARNING: A DISCOURSE-BASED STUDY OF PUBLIC SIGNS IN PADANG - Oktavianus Oktavianus; Zulprianto Zulprianto; Ike Revita; Novalinda Novalinda; Ferdinal Ferdinal; Kamelia Sari; Mita Handayani; Suci Handayani (Universitas PGRI Sumatera Barat, 2025)
This study investigates the role of the English Linguistic Landscape as a potential learning medium for English as a Foreign Language (EFL) in Padang, West Sumatra. While previous studies have described the English Linguistic Landscape in Indonesia, few have explicitly explored its pedagogical value and discursive implications for language learning. Using a mixed-methods approach, the research analyzed 850 English-containing public signs across the city and surveyed 114 EFL students at Universitas Andalas regarding their perceptions of English in public spaces. We examined the signs regarding linguistic units (as the texts) and their visual positioning and relation to symbolic meaning and cultural identity. Findings reveal that English is prominently used in commercial signage, often in larger fonts and strategic positions, signaling its dominance and symbolic prestige over Indonesian. Student responses indicate generally positive attitudes, with more than 80% acknowledging that the English Linguistic Landscape contributes to vocabulary building, grammar awareness, and motivation for language learning. However, the study also notes grammatical and hybrid construction inaccuracies that may reinforce non-standard English patterns. The discussion highlights English Linguistic Landscape as a discourse resource that reflects globalization, power relations, and shifting identities in urban Indonesia. Implications suggest that the English Linguistic Landscape can be integrated into EFL pedagogy through critical analysis tasks and multimodal learning activities. Future research should expand to the digital English Linguistic Landscape and comparative contexts across Indonesian cities. This research underscores the pedagogical and sociocultural significance of the English Linguistic Landscape, though further work is needed to deepen its discourse analysis and pedagogical applications.